SHATTERING THE FALLACY OF THE “DREAM LAND” BRITAIN IN WINSOME PINNOCK’S” LEAVE TAKING” - Adar Bahri; Amel Mahmoud (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ)
The current article deals with Winsome Pinnock’s Leave Taking (1987), a play that comes fertile with diverse themes relevant to immigration, racism, poverty, and identity crisis. However, the analysis lays more focus on the bitter disappointment of Jamaican immigrant Enid and her family in the UK. This cruel reality radically altered the former dreams about the UK being the land of dreams where all one’s misery and poverty come to an end. The discussion in this article seeks to clarify Pinnock’s depiction of the complex and multifaceted challenges experienced by Enid and her family members. Enid and her daughters face financial challenges, racial discrimination, and identity crises living for many years in what they perceive as a new homeland, the UK. Enid immigrates to the UK in search of better living conditions, but the harsh reality of immigration seen in low-wage work, expensive life demands, and racial discrimination gradually destroys her idealized expectations of the UK as a dreamland. This disillusionment with the UK, alongside economic hardship, accentuates the immigrants’ emotional and cultural isolation, as their dreams clash with the harsh reality of their everyday challenging experiences. The methodological framework utilized in this article is the postcolonial theory. The study utilizes concepts and notions from the postcolonial discipline in order to probe through vital thematic elements in this play. Among the key figures in the postcolonial literary discipline are Edward Said (1935-2003), Franz Fanon (1925-1961), and Homi Bhabha (1949- ). The analysis of the play incorporates specific notions Said addresses in his well-reputed book Orientalism (1978). Among the vital ideas are the superiority of the white colonizers and the cruel exploitation of the wealth and richness of the colonies leaving the natives in debilitating conditions. Furthermore, this methodological framework permits an inspection of the feeling of inferiority endured by the black immigrants owing to the color of their skin. This significant idea is thoroughly and expansively discussed by Fanon in many of his books, such as Black Skin, White Masks (1952) and The Wretched Earth (1961).  In The Location of Culture (1994), the hybrid identity is another key aspect that is explored by the postcolonial critic Homi Bhabha. The article cultivates Bhabha’s discussion on identity problems while scrutinizing the feeling of alienation and estrangement the characters in this play constantly struggle with.  Such feelings compel them to view themselves as foreigners in what they mistakenly thought to be their new homeland.